Pemberdayaan Ekonomi Kreatif Masyarakat Pada Masa Pandemi Covid-19 Di Desa Karang Sari, Belitang - Nurma, Nurul Mahmudah; Viki, Viki Ainur Veli Katana; Julduz, Julduz R. Paus (Madani: Jurnal Pengabdian Ilmiah, 2020)
IAIN Metro Community Service Lecture from Home (KPM-DR) is a community service activity in their own area which is carried out from home considering the situation and conditions of Covid-19 as the implementation of Tri Darma College. KPM-DR was implemented as a form of strengthening awareness and concern for the COVID-19 outbreak, proper religious and health relations, religious moderation, and education and Islamic religious preaching by utilizing various social media. The implementation of KPM-DR starts from 1 July to 29 August 2020 in Karang Sari village, Belitang. Programs carried out in the village of Karang Sari, Belitang include socializing Covid-19, teaching the Koran, group exercises, and various other activities. Whereas in the daily activities of individuals, namely making educational videos, posters and blogs containing discussions about wise strategies in managing finances in the midst of the Covid19 pandemic, making plant verticulture, etc. The entire content is uploaded to the social media YouTube, Facebook, blog and Instagram aimed at the social media user community